The Potency of Probiotic as Adjuvant Therapy on The Treatment of Autistic Spectrum Disoders (ASD) - Khoiria Qodriani, Titisari; Setiani, Ariana (The Journal of The Indonesian Medical Students Association, 2010)
Autistic Spectrum Disorders (ASD) is a neurodevelopment disorder which the case increases continously. Recent studies have proved the linkage between gut dysfunction and central nervous system disorders (gut-brain axis) through immunoexcitotoxic mechanism. The overgrowth of pathogen bacteria such as Clostridia in ASD childrenss intestine produce neurotoxin and induce chronic local inflammation. It stimulates the increasing of proinflammatory cytokines level and activation of microglia which induce neural damage. Moreover, dipeptidyl peptidae IV (DPP IV) deficiency in most ASD children increase exorphine level in the bloodstream which induces the presence of some ASD symptoms. Probiotic is potential in preventing gut-brain axis disorders by inducing immunomodulation and exorphine degradation as well as reducing microglial activation. Therefore, it can be an adjuvant therapy for ASD.Key words: autism, autistic spectrum disorders, probiotic.